From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2014)
Co-sonication of curcumin and acidic sophorolipid in aqueous solution is shown to lead to a dramatic enhancement of curcumin bioavailability through size reduction and encapsulation. The interaction between the two is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, FE-SEM, TEM, Infrared spectroscopy and X-ray diffraction measurements. The cytotoxicity effects of curcumin on breast cancer cell lines, MCF-7 and MDA-MB-231, are shown to be significantly enhanced by the formation of its complex with sophorolipid. The relative cytotoxicity of curcumin with its SL(A) complex is more due to the presence of the glucose moiety. The results further suggest that sophorolipid based formulations, which solubilize and nano-encapsulate curcumin after lipid digestion, show great potential for curcumin cell entry.

From waste paper basket to solid state and Li-HEC ultracapacitor electrodes: a value added journey for shredded office paper - Puthusseri, Dhanya; Aravindan, Vanchiappan; Anothumakkool, Bihag; Kurungot, Sreekumar; Madhavi, Srinivasan; Ogale, Satishchandra (Small, 2014)
Hydrothermal processing followed by controlled pyrolysis of used white office paper (a globally collectable shredded paper waste) are performed to obtain high surface area carbon with hierarchical pore size distribution. The BET specific surface area of such carbon is 2341 m 2 g(-1). The interconnected macroporous structure along with the concurrent presence of mesopores and micropores makes the material ideal for ultracapacitor application. Such waste paper derived carbon (WPC) shows remarkable performance in all solid-state supercapacitor fabricated with ionic liquid-polymer gel electrolyte. At room temperature, the material exhibits a power density of 19 000 W kg(-1) with an energy capability of 31 Wh kg(-1). The Li-ion electrochemical capacitor constructed using WPC as cathode also shows an excellent energy storage capacity of 61 Wh kg(-1)

Functionally engineered egg albumen gel for quasi-solid dye sensitized solar cells - Kelkar, Sarika A.; Pandey, Komal; Agarkar, Shruti A.; Saikhedkar, Nidhi; Tathavadekar, Mukta; Agrawal, Ishita; Gundloori, Rathna V. N.; Ogale, Satishchandra (ACS Sustainable Chemistry & Engineering, 2014)
In this report, we demonstrated an interesting application of a bioderived material for the dye sensitized solar cells (DSSCs). Egg white, the clear liquid in a hen's egg, which possesses a remarkable gelling/cross-linking ability, was applied in the form of a gel electrolyte in a DSSC architecture to enhance its durability. A hybrid gel composed of poly(acrylic acid), polyaniline and egg albumen was synthesized, and the cell efficiency, stability and durability of the corresponding DSSC device were studied in detail. The dye sensitized solar cell with the egg albumen based electrolyte demonstrated a conversion energy efficiency of 4.6%. Further, a chemically modified egg albumen with ethylenediaminetetraacetic dianhydride showed improved cross-linking, microstructural and conductivity properties of the gel, and yielded a remarkable 5.75% conversion efficiency. Electrochemical impedance spectroscopy data showed favorable characteristics for charge transport through the modified gel and supported the efficiency observations very well.
Keywords: dye sensitized solar cells; Egg albumen; gel electrolyte

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy (vol 4, pg 60334, 2014) - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2015)